48. KNOWLEDGE AND ATTITUDE OF NURSES ON FALL PREVENTION FOR PATIENTS AT SON TAY GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current situation and study some factors related to knowledge, determine the relationship between knowledge and attitudes of nurses about fall prevention for patients at Son Tay General Hospital in 2025.Method: Cross-sectional descriptive study on 168 nurses of Son Tay General Hospital. Data were collected by self-administered questionnaires and analyzed using SPSS 26.0 software, using Chi-square tests to determine the relationship.Results: Regarding knowledge, 60.1% of nurses had satisfactory knowledge about fall prevention. The rate of achieving knowledge about the definition of falls was 98.8% and about fall prevention measures was 76.2%. Knowledge about risk factors and management, assessment of fall risk was limited, reaching only 41.1%. Regarding attitude, 91.7% of nurses had a positive attitude towards fall prevention. The majority of nurses were concerned about this issue (97%), were willing to help patients (98.2%), and were aware of the need for fall prevention training (95.8%). Factors related to knowledge included: nurses’ knowledge update, knowledge of the hospital’s fall prevention program, which were related to nurses’ knowledge (p < 0.05). Those with satisfactory knowledge had a higher positive attitude than those with inadequate knowledge (p < 0.05).Conclusion: Nurses’ knowledge is limited, however, their attitude is quite good. Therefore, it is necessary to increase updating and training to provide information on fall prevention for nurses in hospitals.
Keywords: Fall prevention, nursing, Son Tay General Hospital, knowledge, attitude, falls.